**Harnessing Digital Transformation for Sustainable Performance in Viet Nam: Exploring the Mediating Roles of Green Knowledge Acquisition and Innovation Performance under Digital Transformational Leadership** - Loc, Luu Duc; Ky Nam, Bui Phuoc; Thuc, Le Huynh Phuong (Global journal of Business and Integral Security, 2026)
Organizations increasingly pursue digital transformation to achieve sustainable performance objectives, yet the underlying mechanisms remain poorly understood. Research indicates that only 35% of companies achieve their digital transformation goals (BCG, 2021), highlighting significant implementation gaps. This study investigates how Green Knowledge Acquisition and Innovation Performance mediate the relationship between digital transformation and sustainable performance, with Digital Transformational Leadership as a moderating factor. Using a quantitative cross-sectional design, we propose to survey 250-300 managers from manufacturing, energy, and logistics industries. The research employs Partial Least Squares Structural Equation Modeling (PLS-SEM) with bootstrapping for mediation analysis. Expected contributions include theoretical integration of knowledge management and leadership perspectives within digital-sustainability frameworks, practical insights for twin transition strategies, and policy recommendations for sustainable digital transformation in emerging market contexts.